TECHNICAL AND ECONOMIC RATIONALE FOR WASTE RECYCLING IN UKRAINE (Economic journal of Lesya Ukrainka Volyn National University, 2021)
Introduction. In Ukraine, the most common methods of waste management are active processing - incineration, utilization (mechanical and biological treatment), and passive storage of their inert residues in specially designated areas. According to European standards, these technologies to some extent carry environmental risks and do not belong to full-fledged recycling. Significant volumes of accumulated and generated waste determine the regional economic potential that can be used for the introduction of recycling technologies. The purpose of the article. The purpose of the article is the feasibility study of waste processing in Ukraine given the regional potential for the development of recycling technologies. To achieve this goal, the following tasks were solved: to analyze the existing technologies for processing household and similar waste and to carry out their economic evaluation; identify areas for innovative development of regional waste management systems in the near future. Results. The analysis of existing in Ukraine technologies of processing of household and similar wastes is carried out. It is emphasized that there are a number of problems with their functionality. Emphasis is placed on the availability of powerful raw materials for the implementation of recycling. The main problems of waste disposal sites are highlighted: lack of their certification due to non-compliance with current standards and continued accumulation of waste despite the exhaustion of service life; voluntary decisions to close technogenic risk landfills; finding alternative ways of waste management. A comparative ecological and economic assessment of waste processing technologies has been carried out. Conclusions. Relevant for the development of waste management system is the use of innovative technologies of waste incineration through reconstruction and equipping of processing plants with modern combustion and filtration systems of exhaust gases to minimize environmental risks.
Keywords: foreign economic activity, agricultural enterprise, agro-industrial complex, export, import, foreign trade balance.